The Implementation of Differentiated Instruction on English Subject: a Case Study - Ningtyas, Safitri Mariyanti; Lestari, Lies Amin (RETAIN : Journal of Research in English Language Teaching, 2024)
This study aimed to describe the implementation of differentiated instruction in teaching English to 7th-grade students and to identify the challenges faced by teachers during the process. This qualitative research uses a case study design involving classroom observations, teacher interviews, and analysis of related documents. The subject of this study is an English teacher at a public junior high school in Lamongan who has been implementing differentiated instruction for one year. The results show that the teacher has a good understanding of the concept of differentiated instruction. The steps taken by the teacher include identifying students' learning needs through diagnostic assessments, adjusting the content and process of teaching, grouping students based on their abilities and learning preferences, and providing constructive feedback. The challenges faced include difficulties adapting materials for different classes and the lack of time to determine the differentiation process. Overall, this study provides an in-depth insight into the practice of implementing differentiated instruction in English classes and the challenges faced by teachers.